STRATEGIC MANAGEMENT CONTROLS AND OPERATIONAL PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN SOUTH-WEST NIGERIA - Yusuf Alabi Olumoh (Malete Journal of Accounting and Finance, 2024)
Small and Medium Enterprises (SMEs) in South-West Nigeria often face performance challenges due to inadequate strategic formulation, ineffective implementation, and insufficient evaluation, leading to resource underutilization and growth obstacles. This study investigated the impact of strategic management controls on SMEs' operational performance in the region. This study adopted a quantitative survey research design and collected primary data from 399 SMEs in South-West, Nigeria, selected through stratified random sampling. Partial Least Squares Structural Equation Modeling was used for data analysis. The findings revealed a significant positive relationship between strategic planning and operational performance (β = 0.233, p = 0.010), indicating the importance of strategic planning in enhancing performance. Additionally, strategic planning had a substantial impact on operational performance (β = 0.373, p = 0.000), demonstrating its effectiveness in driving improvements. Strategic evaluation also had a positive and significant influence on operational performance (β = 0.243, p = 0.000), highlighting its role in performance enhancement. The study concluded that strategic management controls are strong predictors of SMEs' operational performance. The study recommended that SMEs focus on improving their strategic planning processes and invest in robust evaluation processes to assess the effectiveness of implemented strategies and make informed decisions for future endeavors.